Vulnerability of water infrastructure in urban communities A comparison of cities within Europe - Taraldsson, Andrea; Hutchinson-Kay, Olivia (My University, 2024)
Water distribution is a vital part in an urban society. The water distribution infrastructure contributes to multiple necessary functions, the most vital being potable water distribution to the inhabitants. Analyzing the vulnerabilities to this system can be an important part of it is function. In this thesis a further comparison of this subject will be made through three European cities; Berlin, Gothenburg, and London. Previous research is presented to give an understanding of the current systems in the respective cities, research is used to look further into the possible vulnerabilities for these cities. Later a comparison of the three cities' vulnerabilities and future possibilities is made. To gather material and research a qualitative document analysis has been condoned to answer the research questions. Through the qualitative document analysis literature was gathered and an expert interview was performed. The main result from this study; the impact of precipitation on the water supply systems and urbanization expansion problematics is discussed.
Keywords: Water infrastructure; Water supply systems; Urban water planning; Urban flooding; Precipitation